Importance of Probiotics in Orthodontics - Chaturvedi, Saurav; Jain, Upendra (Journal of Orofacial Research, 2015)
White spot lesion (WSL) development of the enamel surface is by far the most important iatrogenic effect of fixed orthodontic appliance therapy and can have lasting negative effects on dental esthetics. The complex design of orthodontic bands and brackets may create an ecological environment that facilitatesthe establishment and growth of cariogenic mutans streptococci strains which are prominent among WSL causative organisms. They are most prevalent around the cervical region of bands in the posterior region, whereas in the anterior region, the lateral incisors in both arches, followed by the canines, are most commonly affected. Various antimicrobials are used to prevent WSL but are not effective long-term unless their application is periodically repeated. Probiotics are live microorganisms which when administered in adequate amounts (in food or as a dietary supplement) confer a health benefit on the host. Various studies have shown that the use of oral probiotics is associated with prevention of white spot lesions and improvement in periodontal health.